Dissection of the Genetic Architecture for Quantities of Gliadins Fractions in Wheat (Triticum aestivum L.) - Zhou, Zhengfu; Geng, Shenghui; Guan, Huiyue; Liu, Congcong; Qin, Maomao; Li, Wenxu; Shi, Xia; Dai, Ziju; Yao, Wen; Lei, Zhensheng; Wu, Zhengqing; Hou, Jinna (Frontiers in Plant Science, 2022)
Gliadin is a group of grain storage proteins which confer extensibility/viscosity to dough and they are vital to end-sue quality in wheat. Moreover, gliadins are one of the important components for nutritional quality due to their containing of the nutritional unprofitable epitopes which cause chronic immune-mediate intestinal disorder in genetically susceptible individuals designated celiac disease (CD). The main genetic loci encoding the gliadins were revealed by previous studies, however, the genes related with the content of gliadins and its fractions were less elucidated. To illustrate the genetic basis of the content of gliadins and its fractions comprehensively, a recombinant inbred line (RIL) population consisted with 196 lines was constructed from the two parents, Luozhen No.1 and Zhengyumai 9987. Quantitative trait loci (QTL) controlling the content of total gliadins and its fractions (ω-, α- and γ- gliadin) were screened genome-widely under four environments across two years. Totally, thirty QTL which explained 1.97% - 12.83% of the phenotypic variation were detected distributing on 17 chromosomes and they were gathered to 12 clusters. One hundred and one pairs of epistatic QTL (E-QTL) were revealed, among which five were involved with the total gliadins and its fractions content QTL located on chromosome 1AS, 1DS, 4DS, 1DL and 6AS. Three KASP (Kompetitive Allele-Specific PCR) markers were developed from 3 major QTL clusters located on chromosome 6A, 6D and 7D, respectively. The present research not only dissects the genetic loci for improving the content of gliadins and its 3 fractions, but may also contribute to marker-assisted selection of varieties with appropriate gliadin fractions content for end-use quality and health benefit at the early developmental stages and early breeding generations.